Strategi Pengembangan Profesionalisme Guru dalam Konteks Manajemen Berbasis Sekolah Dasar di Era Digital - Novelita, Nevi; Devian, Lora; Sufyarma, Sufyarma; Rifma, Rifma (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The background of the problem in this article is the need to analyze the strategies for developing teacher professionalism in the context of school-based management at the elementary level in the digital era. The aim of this article is to analyze the strategies, benefits, challenges, and impacts of using technology on the development of teacher professionalism within the context of school-based management at the elementary level in the digital era. This article employs a qualitative research method, utilizing interviews with five teachers and analyzing recent literature. The research procedure involved structured interviews with teachers involved in professionalism development, as well as data collection and analysis using thematic coding. The findings and discussions indicate that strategies for developing teacher professionalism through technology utilization in the context of school-based management at the elementary level in the digital era have been identified. The challenges include limited access, inadequate training, and privacy concerns. However, the benefits include access to extensive educational resources, global collaboration, and increased student engagement. The use of technology also has a positive impact on improving the quality of teaching and the efficiency of school-based management. As a recommendation, support and collaboration among schools, government, and stakeholders are necessary to ensure effective and equitable utilization of technology in the context of elementary education.